Health vs. privacy. How Norwegian public authorities and news media framed the newly developed digital contact tracing app “Smittestopp” under the COVID-19 pandemic - Karlberg, Anne-Maren; Magin, Melanie (Frontiers in Communication, 2023)
In spring 2020, shortly after the outbreak of the Coronavirus diseases 2019 (Covid-19), Norway introduced the digital contract tracing app “Smittestopp” (“Stop infection”) as a measure to combat the pandemic. The launch was accompanied by scientific uncertainties about the technology: The app had been developed at lightning speed and hardly been tested, and its effects were unclear. It did not become a success, was strongly underused and soon had to be discontinued due to privacy issues. Our study starts from the assumption that in this situation of uncertainty about the technology, combined with and resulting from a lack of user experience, the app’s public portrayal was a decisive factor for this outcome. We investigate the framing of “Smittestopp” in press releases by Norwegian public authorities and in news articles. By means of a qualitative content analysis, we identify eleven frames and uncover the opposition between health considerations and privacy concerns as central conflict line. In their press releases, the public authorities did not use frames very strategically. The news media provided diverse frames but at the same time focused relatively strongly on privacy issues that ultimately led to the app’s discontinuation.